Antibacterial efficacy of Bacopa monnieri leaf extracts against pathogenic bacteria - Khan, Abdul Viqar; Ahmed, Qamar Uddin; Shukla, Indu; Khan, Athar Ali (Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand., 2010)
Background: Bacopa monnieri (Linn) Pennell (Scrophulariaceae) is widely distributed in tropical regions of Asia, and used in the treatment of cough or as an antiseptic. The traditional use of this plant suggests its possible antibacterial properties, but its efficacy has not been examined yet. Objective: Evaluate the antibacterial efficacy against pathogenic bacteria using the disk diffusion method. Materials and methods: Five different concentrations (500 μg, 1, 2, 5, 10, and 15 mg/mL) of crude leaf extracts of Bacopa monnieri (L.) Pennell were tested for antibacterial efficacy against seven Gram-positive and 11 Gramnegative bacteria. The sensitivity of plant fractions was tested using the disk diffusion method. Results: Maximum activity was revealed by ethyl acetate and methanol extracts, followed by aqueous, benzene, and petrol extracts. Phyto-chemical analysis of the plant leaf showed the presence of alkaloids, flavonoids, and saponins. Conclusion: This plant may be effective for treatment of different pathogenic diseases. Keywords: Antibacterial efficacy, Bacopa monnieri (L.) Pennell, crude extracts, traditional use